On Sonic Art - Wishart, Trevor; Emmerson, Simon (New York Routledge, 1996)
In the book On Sonic Art, Trevor Wishart discussed new musical possibilities offered by these tools, and developed notion of a sophisticated art of sound, or Sonic Art. In particular, put forward the ideas of sound landscape (handling sound images and representation using sound), and sound transformation as a unifying principle for composing, traditionally or with sounds.
A New and Revised Edition
Keywords: Acoustics